Molecular Imaging of Striatal Dopaminergic Neuronal Loss and the Neurovascular Unit in Parkinson Disease - Ivanidze, Jana; Skafida, Myrto; Pandya, Sneha; Patel, Dylon; Osborne, Joseph R.; Raj, Ashish; Gupta, Ajay; Henchcliffe, Claire; Dyke, Jonathan P. (Frontiers in Neuroscience, 2020)
Parkinson Disease (PD) is the second most common neurodegenerative disorder, characterized by loss of nigrostriatal dopaminergic neurons. Impairment of the neurovascular unit (NVU) has been hypothesized to play a critical role in early PD pathophysiology, and to precede neurodegenerative mechanisms. [C-11]-PE2i (N-(3-iodoprop-2E-enyl)-2b-carbomethoxy-3b-(4-methyl-phenyl)nortropane) (PE2i) is a PET radiotracer targeting neuronal dopamine transporters (DaT) with high specificity, allowing for highly accurate and specific DaT quantification. We investigated NVU integrity using arterial spin labeling (ASL) MRI in a prospective cohort of 26 patients with PD, and correlated our findings with analysis of striatal DaT density using PE2i PET in a subcohort of 17 patients. Analysis was performed in FreeSurfer to obtain rCBF and mean standardized regional PET avidity. Pearson correlations and Mann-Whitney tests were performed. Significantly lower mean normalized striatal PE2i SUV values were seen in multiple regions in patients with greater disease duration (p < 0.05). PET uptake in the putamen correlated with disease duration independent of patient age. Stratifying patients based on MoCA scores (stratified into 27 or greater vs <27), there was statistically significantly lower PE2i PET avidity in the higher MoCA score group in both more and less affected sides of the caudate, putamen and pallidum (p < 0.05). A moderate negative correlation between MDS-UPDRS part 3 (motor) "off" and rCBF values was also seen in the L and R cerebellum WM (r=-0.43 and -0.47, p<0.05). A statistically significant negative correlation was found between dominant hand pegboard test results and rCBF in the less affected pallidum (r=-0.41; p=0.046). A statistically significant negative correlation of ASL MRI with [11C]-PE2i PET was also found (r=-0.53 to -0.58; p-value 0.017-0.033) between left cerebral WM rCBF and more and less affected striatal PET regions. Our ROI-based analyses suggest that longer disease duration is associated with lower rCBF and lower PE2i mean SUV, implying greater NVU dysfunction and dopaminergic neuronal loss, respectively. Combined ASL MRI and PE2i PET imaging could inform future prospective clinical trials providing an improved mechanistic understanding of the disease, laying the foundation for the development of early disease biomarkers and potential therapeutic targets.